Numerical Investigation of Hydrokinetic Savonius Rotor with Two Shielding Plates - M. Hemida (Applications of Modelling and Simulation, 2019)
Savonius hydrokinetic rotor is an evolution of the conventional savonius wind turbine. This rotor is suitable for low flow velocities with simple design, high starting torque and working for all flow directions. However, the torque fluctuation of this rotor is a serious problem due to the negative moment generated at the returning blade of this rotor. In this paper, a numerical investigation with commercial computational fluid dynamic (CFD) package FLUENT for modified savonius rotor with two deflector plates in the upstream of the turbine is conducted to find the optimum position of the two deflector plates to increase the power coefficient using water as a working medium. Results show that the model with the best orientation of the two deflector plates in the upstream increases the power coefficient by 80%. This may be due to the overlapped effect of decreasing the negative moment on the returning blade and the increased flow velocity at the advancing blade.